Às margens do Império: a pecuária das carnes salgadas e o comércio nos portos da porção oriental da costa leste oeste da América portuguesa nas dinâmicas de um império em movimento (Século XVIII) - Nogueira, Gabriel Parente (2021)
Throughout the 18th century, the eastern portion of the east-west coast – the coastal region of Portuguese America located between Cape of São Roque and the Parnaíba delta – had its history marked by the emergence of port cores distributed between the territories of the captaincies of Rio Grande do Norte, Siará-Grande and São José do Piauí, which developed from the exploitation of commercial activities based on the production of salted meat and other cattle by-products; exported genuses on small vessels that, through coastal shipping, connected these ports to the main economic centers of Portuguese America. The salted meat trade developed in these centers, known at the time as “ports of the hinterland”, was largely driven by traders who integrated or maintained close ties with the mercantile community of Recife. This work broadly and jointly analyzes the historical experience of salted meat production in the ports of the hinterland based on some great dynamics experienced in the Atlantic portion of the Portuguese empire in the 18th century. Among other aspects, it is demonstrated that both the emergence of these activities in the region at the beginning of the 18th century, and the beginning of its process of disruption at the end of the century, occurred in contexts marked by profound transformations, both in some important consumption bases of this genre in Portuguese America, as well as in the regional base that gave support to the organization of these activities: the general captaincy of Pernambuco, a space over which, preferably, the mercantile/commercial influence of praça do Recife was extended in the 18th century.